Clinical utility of SUDOSCAN in predicting autonomic neuropathy in patients with Parkinson's disease. (July 2019) - Xu, Xiaofeng; Liao, Jinchi; Dong, Qing; Qin, Feng; Li, Jing; Sun, Xiaobo; Lu, Tingting; Fang, Ling; Peng, Fuhua; Lu, Zhengqi; Qiu, Wei
Abstract: Introduction: Autonomic neuropathy is common in Parkinson's disease (PD). We evaluated whether SUDOSCAN, a novel electrophysiological device that provides a simple and quantitative assessment of sudomotor function, was able to detect PD-related autonomic neuropathy. We also used the device to examine potential risk factors for PD-related autonomic neuropathy. Methods: Forty-three hospitalized patients in the later stages of PD underwent assessments including a clinical history, the Unified Parkinson's Disease Rating Scale (UPDRS), the Scale for Outcomes in Parkinson's disease for Autonomic Symptoms (SCOPA-AUT), and measurement of homocysteine (HCY) and vitamin B12 levels. Sudomotor function was assessed by measuring electrochemical skin conductance (ESC) using SUDOSCAN. Forty-two healthy participants served as controls. Results: ESC of the limbs, and especially the hands, was significantly lower in PD patients than in controls and was significantly correlated with SCOPA-AUT results. ESC was strongly negatively correlated with PD duration. The results also indicated that levodopa exposure and a higher HCY level may be risk factors for PD-related autonomic neuropathy. Conclusions: SUDOSCAN was able to effectively identify autonomic neuropathy in PD patients. ESC was decreased in PD patients and was correlated with PD-related autonomic symptoms. These findings suggest that SUDOSCAN could be a promising new method for assessing PD-related autonomic neuropathy. Highlights: SUDOSCAN is a promising method to detect autonomic dysfunction in later stages of PD. ESC values are correlated with the extent and severity of autonomic symptoms of PD. LD exposure and HCY level may be risk factors for PD-related autonomic neuropathy.